1996
DOI: 10.7863/jum.1996.15.11.747
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile lower limb venous Doppler flow: prevalence and value in cardiac disease diagnosis.

Abstract: The purpose of this study was to assess the frequency and significance of pulsatile Doppler waveforms in lower limb veins. We used Doppler sonographic data from the common femoral vein. In the first of two groups, the findings in 250 patients were correlated with the presence of cardiac decompensation on concurrent chest radiographs. In the second group, the findings in 81 patients were correlated with the presence of tricuspid regurgitation on Doppler echocardiograms. A venous Doppler sonographic examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 2 publications
1
17
1
Order By: Relevance
“…Previous studies have reported reverse pulsatile flow in lower extremity veins, which has been attributed to diseases characterised by right atrial pressure elevation 2 3. In the present case, reverse pulsatile flow caused by right atrial pressure elevation secondary to right-sided heart failure was transmitted to the femoral vein, striking the venous valve in retrograde fashion, and creating turbulent jet flow.…”
Section: Answer: Csupporting
confidence: 48%
“…Previous studies have reported reverse pulsatile flow in lower extremity veins, which has been attributed to diseases characterised by right atrial pressure elevation 2 3. In the present case, reverse pulsatile flow caused by right atrial pressure elevation secondary to right-sided heart failure was transmitted to the femoral vein, striking the venous valve in retrograde fashion, and creating turbulent jet flow.…”
Section: Answer: Csupporting
confidence: 48%
“…In that study, the sensitivity of venous Doppler sonography for detecting cardiac abnormalities was 79%, the specificity was 87%, and the accuracy was 84%. 3 Abu-Yousef et al 1 reported that the sensitivity of lower-limb venous Doppler imaging for detecting right-sided heart failure as determined by right atrial pressure measurements was 46%, the specificity was 94%, the negative predictive value was 50%, and the accuracy was 65%. The authors noted that pulsatile lower-limb venous Doppler waveforms corre- late well with right-sided heart failure, as indicated by a right atrial pressure measurement above 8 mm Hg.…”
Section: Discussionmentioning
confidence: 99%
“…1 In these previous studies, pulsatility of the waveforms was not quantified. 1,3 Cardiac phasicity in lower-limb venous Doppler tracings, however, does not necessarily indicate cardiac disease. Minimal cyclic retrograde flow that is 5 cm/second or less can be observed in Doppler tracings of the CFV in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right CFV was the only one studied since it is quite close to the heart and is less affected by DVT, [8][9][10] and, if distal thrombosis exists, it does not affect the waveform. 11 The venous wave spectrum was obtained by adequately angling the ultrasound probe (less than 60 degrees). The wall filter was the lowest possible level, and the PRF was adjusted manually to the lowest level to avoid aliasing.…”
Section: Methodsmentioning
confidence: 99%